ANXIETY OF DANNY ARCHER REFLECTED IN EDWARD ZWICK 'S BLOOD DIAMOND (2006): A PSYCHOANALYTIC APPROACH - DARYANTO, ENI ASRINING (2011)
The major problem of this study is how anxiety is reflected in the major character‟s personality. The aim of this study is to analyze Edward Zwick's Blood Diamond based on the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Danny Archer. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Blood Diamond movie directed by Edward Zwick released in 2006. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis, the outcome of this study shows that the problem of major character encounters causes the conflict of his mental condition. Then, it develops to become anxiety and influences him to do some ways to escape from it. Then his ways are not effective to overcome the problem because finally he can find the way to decide the right thing.